Patronin governs minus-end-out orientation of dendritic microtubules to promote dendrite pruning in Drosophila - Yan Wang; Menglong Rui; Quan Tang; Shufeng Bu; Fengwei Yu (eLife, 2019)
Class IV ddaC neurons specifically prune larval dendrites without affecting axons during Drosophila metamorphosis. ddaCs distribute the minus ends of microtubules (MTs) to dendrites but the plus ends to axons. However, a requirement of MT minus-end-binding proteins in dendrite-specific pruning remains completely unknown. Here, we identified Patronin, a minus-end-binding protein, for its crucial and dose-sensitive role in ddaC dendrite pruning. The CKK domain is important for Patronin’s function in dendrite pruning. Moreover, we show that both patronin knockdown and overexpression resulted in a drastic decrease of MT minus ends and a concomitant increase of plus-end-out MTs in ddaC dendrites, suggesting that Patronin stabilizes dendritic minus-end-out MTs. Consistently, attenuation of Klp10A MT depolymerase in patronin mutant neurons significantly restored minus-end-out MTs in dendrites and thereby rescued dendrite-pruning defects. Thus, our study demonstrates that Patronin orients minus-end-out MT arrays in dendrites to promote dendrite-specific pruning mainly through antagonizing Klp10A activity.Editorial note: This article has been through an editorial process in which the authors decide how to respond to the issues raised during peer review. The Reviewing Editor's assessment is that minor issues remain unresolved (see decision letter).